1934
DOI: 10.1001/jama.1934.02750010017004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Heart Disease by Lowering the Metabolic Rate

Abstract: titis while working with tobacco in North Carolina, but on two occasions, while buying tobacco in Kentucky, had such an eruption. This example illustrates the statement made by one of the discussers that tobacco from different sections of the country may possess different allergic properties.Dr. Marion B. Sulzberger, New York : I think the applition of skin tests in many conditions in which no one has thought of applying them may lead to further knowledge. To know when, where and how to apply these tests, what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1934
1934
1937
1937

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 14 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Blumgart and his associates (3) (4) (5) (6) have shown that in patients without thyroid disease, complete removal of the normal thyroid must be performed to assure a persistently subnormal basal metabolic rate. To accomplish complete ablation of the thyroid gland, the region of the parathyroid bodies must be deliberately invaded.…”
mentioning
confidence: 99%
“…Blumgart and his associates (3) (4) (5) (6) have shown that in patients without thyroid disease, complete removal of the normal thyroid must be performed to assure a persistently subnormal basal metabolic rate. To accomplish complete ablation of the thyroid gland, the region of the parathyroid bodies must be deliberately invaded.…”
mentioning
confidence: 99%